2018
DOI: 10.3390/rs10122007
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Season Crop Height Variability at Commercial Farm Scales Using a Fixed-Wing UAV

Abstract: Monitoring the development of vegetation height through time provides a key indicator of crop health and overall condition. Traditional manual approaches for monitoring crop height are generally time consuming, labor intensive and impractical for large-scale operations. Dynamic crop heights collected through the season allow for the identification of within-field problems at critical stages of the growth cycle, providing a mechanism for remedial action to be taken against end of season yield losses. With advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 85 publications
0
48
0
2
Order By: Relevance
“…To reduce the cost of estimating crop PH, researchers start to use low-cost UAV RGB remote-sensing system [64][65][66][67]. For example, Ziliani et al [68] compared the PH derived from high-resolution UAV RGB imagery against PH derived from LiDAR, and showed a strong correlation between structure-from-motion derived heights and LiDAR scan data with the coefficient of determination (R 2 ) ranged from 0.77 to 0.99. Grüner et al [69] estimated the PH of grass in northern Hesse, Germany from UAV RGB imagery by using photogrammetric structure from motion processing, and showed a high correlation between PH derived from UAV RGB imagery and ground-truth data with a R 2 value of 0.56 and a root mean squared error (RMSE) value of 0.13 m. In many of these studies, crop surface model derived from point clouds was adopted to estimate PH.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the cost of estimating crop PH, researchers start to use low-cost UAV RGB remote-sensing system [64][65][66][67]. For example, Ziliani et al [68] compared the PH derived from high-resolution UAV RGB imagery against PH derived from LiDAR, and showed a strong correlation between structure-from-motion derived heights and LiDAR scan data with the coefficient of determination (R 2 ) ranged from 0.77 to 0.99. Grüner et al [69] estimated the PH of grass in northern Hesse, Germany from UAV RGB imagery by using photogrammetric structure from motion processing, and showed a high correlation between PH derived from UAV RGB imagery and ground-truth data with a R 2 value of 0.56 and a root mean squared error (RMSE) value of 0.13 m. In many of these studies, crop surface model derived from point clouds was adopted to estimate PH.…”
Section: Discussionmentioning
confidence: 99%
“…To construct the 3D models, photogrammetry requires at least two overlapping images of the same scene and/or object(s), captured from different points of view. These kind of techniques can be used for extracting three-dimensional digital surface or terrain models [37,40,43] and/or orthophotos [50,55]. UAV low-altitude data acquisition enables the construction of 3D models with a much higher spatial resolution compared to other remote sensing technologies (such as satellites).…”
Section: Crop Featuresmentioning
confidence: 99%
“…Adobe Photoshop [21,100] Applied to correct distortion/use of other image processing methods Agisoft Photoscan [22,36,37] Exploited for the construction of 3D models and orthomosaics. It also allows the calculation of vegetation indices QGIS [23,55] Usually exploited for the calculation of the vegetation indices from multispectral data MATLAB [35,100] Applied mainly for the calculation of vegetation indices.…”
Section: Software Tool Descriptionmentioning
confidence: 99%
“…Similar findings were identified in this research, where shape features such as plant area, border length, width and length had the highest importance in the random forest models, followed by the Green-Red Vegetation Index, and the entropy texture feature extracted from a gray level co-occurrence matrix. While crop height, which is generally measurable from UAV imagery, has been identified as an important parameter for predicting crop yield (Ziliani et al, 2018), it was found to be of little importance in the Random Forest models for the six dates assessed in this research. This was attributed to the flattening of tomato plants caused by sandstorms and the fact that once tomato fruits become larger and heavier, the weight is likely to bend branches downwards, potentially reducing plant height.…”
Section: Predicting Biomass and Yieldmentioning
confidence: 77%